Risk Factors of Metabolic Syndrome Among Nurses Hospital Banten, Indonesia - Yulistriani, Anisa; Rayasari, Fitrian; Munaya, Munaya; Jumaiyah, Wati; Abriyanti, Rika Mustika (STIKep PPNI Jawa Barat, 2024)
Aims: This study was to determine the prevalence of metabolic syndrome and its associated factors among nurses in Banten. Methods: The cross-sectional design of this particular type of quantitative correlation study. A total of 102 respondents were comprised of samples selected using random sampling. Variabel aktivitas fisik diidentifikasi menggunakan APARQ (Adolescent Physical Activity Recall Questionnaire) dan Stres diidentifikasi menggunakan DASS 21. Metabolic indicators include hypertension, Obesity, cholesterol, and diabetes. Data analysis used logistic regression. Result: The prevalence of metabolic syndrome among nurses was 16.7%. Older age (p=0.006), smoking (p=0.008), and stress (p=0.000) were significantly associated with metabolic syndrome. While gender and exercise were not significantly associated with metabolic syndrome. Conclusion: smoking and stress were the major modifiable risk factors of metabolic syndrome among nurses. Campaigns and prevention of healthy behavior are crucial even among healthcare professionals.